2022
DOI: 10.1001/jamanetworkopen.2022.0018
|View full text |Cite
|
Sign up to set email alerts
|

Association of Prognostic Understanding With Health Care Use Among Older Adults With Advanced Cancer

Abstract: IMPORTANCE A poor prognostic understanding regarding curability is associated with lower odds of hospice use among patients with cancer. However, the association between poor prognostic understanding or prognostic discordance and health care use among older adults with advanced incurable cancers is not well characterized. OBJECTIVE To evaluate the association of poor prognostic understanding and patient-oncologist prognostic discordance with hospitalization and hospice use among older adults with advanced canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…36 In addition, prognostic discordance regarding curability and life expectancy estimates occurred in 60% and 72% of the dyads respectively, with patients estimating a higher chance of curability and greater life expectancy than their oncologists. 36…”
Section: Discussionmentioning
confidence: 98%
“…36 In addition, prognostic discordance regarding curability and life expectancy estimates occurred in 60% and 72% of the dyads respectively, with patients estimating a higher chance of curability and greater life expectancy than their oncologists. 36…”
Section: Discussionmentioning
confidence: 98%
“…Finally, caregivers can face a number of challenges when trying to support patient treatment decision‐making, particularly understanding the patient's physical condition and quality of life. Studies have shown the benefits of prognostic disclosure discussions, 22,23 hence clinicians should seek to initiate and conduct conversations with patients and families about prognosis and the likely course of the cancer trajectory. A growing body of resources is available to facilitate training in these conversation skills 24,25 …”
Section: Discussionmentioning
confidence: 99%
“…Results indicate that while ACP may not necessarily change patient’s end-of-life trajectory or their end-of-life care, nor does it facilitate end-of-life care consistent with their preferences, it does positively influence their interactions with the healthcare system and with their caregivers. Given that many seriously ill patients and their caregivers do not understand enough about their (patients’) illness and are ill-prepared to make in-the-moment end-of-life decisions,172 173 ACP’s impact on improving communication cannot be considered trivial. ACP should thus not be considered a magic bullet for improving patient’s end-of-life care and reducing end of life healthcare costs, but instead should be considered as a means of facilitating a shared understanding between patients, surrogates and healthcare providers of what matters most to patients, preparing patients and caregivers for the difficult end-of-life decision-making, improving their communication with each other and with their healthcare providers, thereby humanising our healthcare systems.…”
Section: Discussionmentioning
confidence: 99%